2014
DOI: 10.1002/mus.24164
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous activation of rage in nonsystemic vasculitic and diabetic neuropathy

Abstract: Dermal RAGE is increased in NSVN and DN, supporting the concept of a role of the RAGE pathway in the pathophysiology of dermal inflammation and skin denervation in NSVN and DN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…More detailed studies aimed at deciphering the molecular mechanisms by which RAGE exerts its actions in DPN progression, conducted in RAGE-deficient mice after acute peripheral nerve injury, revealed that RAGE, in addition to triggering a cascade of detrimental metabolic changes, contributes to nerve pathology by promoting a switch in macrophage phenotype from anti-inflammatory to proinflammatory at the injury site (Juranek et al, 2013a). Two other recent studies focused on the prognostic measurement and correlation between AGE and RAGE expression in skin biopsies and neurological scores on diabetic neuropathy severity scale in diabetic patients revealed that there is a significant increase in skin biopsy AGE and RAGE levels, which is strongly correlated with neuropathy severity, thus further supporting the role of RAGE in the pathogenesis of this disease (Bekircan-Kurt et al, 2014;Park et al, 2014).…”
Section: Rage In Peripheral Neuropathiesmentioning
confidence: 88%
“…More detailed studies aimed at deciphering the molecular mechanisms by which RAGE exerts its actions in DPN progression, conducted in RAGE-deficient mice after acute peripheral nerve injury, revealed that RAGE, in addition to triggering a cascade of detrimental metabolic changes, contributes to nerve pathology by promoting a switch in macrophage phenotype from anti-inflammatory to proinflammatory at the injury site (Juranek et al, 2013a). Two other recent studies focused on the prognostic measurement and correlation between AGE and RAGE expression in skin biopsies and neurological scores on diabetic neuropathy severity scale in diabetic patients revealed that there is a significant increase in skin biopsy AGE and RAGE levels, which is strongly correlated with neuropathy severity, thus further supporting the role of RAGE in the pathogenesis of this disease (Bekircan-Kurt et al, 2014;Park et al, 2014).…”
Section: Rage In Peripheral Neuropathiesmentioning
confidence: 88%
“…Increased advanced glycation endproducts and RAGE have been described in dermal microvessels and T cells of patients with NSVN; however patients with diabetic neuropathy had similar expression to NSVN patients relative to healthy controls [8], suggesting that this may be a marker of vasculopathy. Another study designed to deduce whether apoptosis played a role in endothelial cell injury in 19 patients with vasculitic neuropathy by immunohistochemistry and terminal deoxynucleotidyl transferase-mediated nick end labeling demonstrated expression of granzyme A, granzyme B and T-cell restricted intracellular antigen, as well as Fas and FasL on epineurial perivascular mononuclear cells by immunohistochemistry, implying that T-lymphocyte and macrophage apoptosis may occur during a phase of peripheral nerve recovery in this disorder [46].…”
Section: Introductionmentioning
confidence: 99%
“…AGE measurement can in fact be made in plasma [ 26 30 ], in urine [ 26 ], or in tissues, skin being the most often used tissue [ 31 , 32 ]. Among several compounds already studied, CML is the best characterized AGE [ 29 ] and the most consistently assessed one in plasma analysis [ 26 30 ].…”
Section: Discussionmentioning
confidence: 99%